Un nuevo modelo de optimización convexa utilizando el cálculo de Wirtinger para despacho económico. - Ortiz Malla, Josue Steeven (2024)
The present work proposes a methodology to the problem of short-term economic dispatch of radial and meshed power systems by means of nonlinear programming (NLP). The problem posed will be solved through the cost function of the classical economic dispatch where hydro, wind generation on the whole with the energy storage system will be included, using the linearized model based on the Wirtinger calculation for obtaining the electrical power generated in each of the nodes. The proposed methodology will be used for a short-term period of 24 hours with different hourly demand; for this case will be developed within the IEEE 14-bus model and brief modifications will be done to the model in order to include the different generation units. Due to the complexity of the system, the linearized model manages to solve it in less time than the traditional model, without having to make simplifications of the system's own characteristics, obtaining as a result the voltages and angles of each of the bars, expressing a minimum error that is the (penalty) for the linearization of the economic dispatch model.